M PROBLEMS AND POSSIBILITIES OF LASER SYNTHESIS OF METAL POWDERS IN ADDITIVE TECHNOLOGIES: PROBLEMS AND POSSIBILITIES OF LASER SYNTHESIS OF METAL POWDERS IN ADDITIVE TECHNOLOGIES - Асатиллаев, Йулдашали; Исроилов, Низомжон (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2023)
Abstract. Objective. To carry out research on the production technology of powder materials used in the production of products with additive technology, to apply the obtained results for the purposes of powder metallurgy. Methods. The mechanical methods of obtaining metal powders are studied in the article, and the properties of formation without significant changes in the chemical composition of the powder material are highlighted. Results. Depending on the aggregate state of the initial components in the reaction zone, results were obtained for three main types of the reaction process: solid-phase, non-gaseous and gaseous types. It was found that during the solid phase reaction, the metal particles in the powder mixture retain their original size. It was found that the reaction rate of gasless combustion does not depend on pressure and the constant mass of the formed particle is maintained. The dependence of the gas combustion reaction rate on pressure and the change in the mass of powder particles during the process were determined. Conclusion . In the process of mechanochemical synthesis, it is necessary to take into account the increase in the volume fraction of the three-sided bond boundary with the decrease in the size of the particles. In the process of preparing the powder material, its positive feature is its low temperature and high speed fusion, while maintaining its plasticity with the reduction of the particle size. The reduction of the particle size reduces the porosity of the powder, which increases the density and strength of the prepared product.